Analysis of Injection Processes in an Innovative 3D-CFD Tool for the Simulation of Internal Combustion Engines - Wentsch, Marlene; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2019)
Due to the large number of influencing parameters and interactions, the fuel injection and therewith fuel propagation and distribution are among the most complex processes in an internal combustion engine. For this reason, injection is usually the subject to highly detailed numerical modeling, which leads to unacceptably high computing times in the 3D-CFD simulation of a full engine domain. Marlene Wentsch presents a critical analysis, optimization and extension of injection modeling in an innovative, fast response 3D-CFD tool that is exclusively dedicated to the virtual development of internal combustion engines. Contents The 3D-CFD Tool QuickSim Numerical Boundary Conditions Liquid Fuel Modeling Parametrization of Injector Properties Target Groups Researchers and students of internal combustion engines Automotive engineers and engine developers About the Author Marlene Wentsch works as research associate in the field of 3D-CFD simulations of injection processes at the Institute of Internal Combustion Engines and Automotive Engineering (IVK), University of Stuttgart, Germany.
The 3D-CFD Tool QuickSim -- Numerical Boundary Conditions -- Liquid Fuel Modeling -- Parametrization of Injector Properties.
Keywords: Automotive engineering; Engines; Computer simulation; Automotive Engineering; Engine Technology; Computer Modelling